Penanggulangan Tindak Pidana Siber Dengan Menggunakan Teori Jendela Pecah - Wenggedes Frensh (DOKTRINA: JOURNAL OF LAW, 2021)
The development of information and communication technology provides positive benefits, such as the emergence of e-learning, e-commerce, e-banking, e-government, e-medicine and others. However, information and communication technology also has a negative impact with the emergence of cybercrime. Internet users in Indonesia in early 2021 reached 202.6 million people, this number increased by 15.5% or 27 million people compared to January 2020. This study aims to determine how to tackle cyber crime in cyberspace by using the broken window theory. The research method used is a normative juridical research method with secondary data sources and analyzed deductively. The results of the study indicate that the prevention of cyber crime in cyberspace can use the broken window theory. The prevention of cyber crime is carried out by maintaining cyber space so that it is maintained like a window with glass. Safeguarding cyberspace to be protected like a window with strong glass is to protect cyberspace using the ITE and Pornography Law that applies, cybersecurity which is guarded by every technology user and cyber police who conduct cyber patrols.